The Importance of Islamic Education Teacher Competence And Parental Attention In Enhancing Students' Character Formation At Nur Al-Jadid ExcellentIslamic High School: The Importance of Islamic Education Teacher Competence And Parental Attention In Enhancing Students' Character Formation At Nur Al-Jadid ExcellentIslamic High School - bagus firmansyah, bagus firmansyah; Didit Darmawan (Jurnal Cahaya Mandalika ISSN 2721-4796 (online), 2023)
This study aims to explore the influence of Islamic Religious Education teacher competence and parental attention on student character building at MA Featured Nur Al-Jadid Waru Sidoarjo. The purpose of this study is to analyse and determine the impact of each of these factors. The research method used a quantitative approach with a survey method, involving 33 students from classes X-XI by census. The research instrument was a questionnaire with variables of Islamic Religious Education teacher competence, parental attention, and student character building. Regression analysis was chosen to identify the relative impact of each variable. Validity and reliability tests were conducted to ensure data quality. The results showed that teacher competence and parental attention had a significant impact on students' character building. Competent teachers create a supportive environment for students' character and parental attention provides a moral foundation for developing social norms. Both factors play an important role in student character formation. This study is expected to contribute to understanding the factors that influence student character formation and provide guidance for education practitioners to improve the effectiveness of character education.